200Pneumonia hospitalization and the subsequent risk of incident ischemic cardiovascular disease in Chinese adults. (2nd September 2021) - Hu, Yizhen; Yu, Canqing; Guo, Yu; Bian, Zheng; Han, Yuting; Yang, Ling; Chen, Yiping; Du, Huaidong; Sun, Dianjianyi; Chen, Junshi; Chen, Zhengming; Lv, Jun; et al.
Abstract: Background: Acute respiratory infections have been associated with a transient increase in cardiovascular risk. However, whether such an association persists beyond one month, and the potential modifying effect of cardiovascular risk factors on such an association is less well established. Methods: The China Kadoorie Biobank study enrolled 512, 726 participants from 10 areas across China during 2004-08. By the end of 2017, a total of 5, 444 participants with ischemic heart disease (IHD) and 4, 846 with ischemic stroke (IS) who also had at least a record of hospitalization for pneumonia during follow-up were included. We used a self-controlled case series method and calculated the age- and season-adjusted relative incidences (RIs) and 95% confidence intervals (CIs) for ischemic cardiovascular disease (CVD) after pneumonia. Results: The risk of ischemic CVD increased during days 1-3 after pneumonia hospitalization, with a RI (95% CI) of 4.24 (2.92-6.15) for IHD and 1.85 (1.02-3.35) for IS. The risk gradually reduced with longer duration since pneumonia hospitalization but remained elevated until days 92-365 for IHD (1.23, 1.12-1.35), and days 29-91 for IS (1.25, 1.05-1.48). Pre-existing cardiovascular risk factors amplified the associations between pneumonia and ischemic CVD risks. Besides, the risk of ischemic CVD was also higher among the participants aged ≥70 years ( P interaction <0.001 for IHD and =0.033 for IS). Conclusions: Among middle-aged and older Chinese adults, pneumonia hospitalization was associated with both short- and long-term increases in ischemic CVD risk for up to one year. Key messages: Pneumonia hospitalizations were associated with increased subsequent risk of ischemic CVD.